Lean adoption, implementation, and outcomes in public hospitals: benchmarking the US and Italy health systems - Marta Marsilio; Martina Pisarra; Karl Rubio; Stephen Shortell (BMC, 2022)
Abstract Background Despite the growing interest in transformational performance improvement among nearly all countries, international benchmarking has rarely been used. Cross-comparative research could allow an appreciation of the extent of Lean's use in healthcare and a better evaluation of possible cultural influences on Lean implementation. This study provides a comparative international benchmarking of Lean adoption, implementation, and outcomes of hospitals in the US and Italy. Methods The National Survey of Lean, developed in 2017 in the US and adapted in Italy in 2019 was used to compare the two healthcare systems along three dimensions: the maturity of adoption, the implementation approach, identifying both strategic and operational activities and tools, and the Lean performance, investigated through patients, employed, and affiliated staff, costs, and service provision areas. Descriptive statistics including T-tests were used to examine differences between the two countries on the study variables. Results Lean has been adopted less by Italian public hospitals (36%) than US public hospitals (53%). Each country averages 4 years of experience with Lean. Italian hospitals reported being at a higher maturity stage while the US implemented a more system-wide approach, developing Lean in more operational units. The daily management system, leadership commitment, education and training indexes were higher or the same in the US while in Italy, hospitals had a higher self-reported performance index. Conclusion This exploratory work is one of the first international benchmarking studies on Lean implementation in healthcare systems using a standardized survey with a common set of definitions and questions. The study identifies different forms of Lean implementation that can be adopted, both at strategic and operational levels, with related perceived outcomes. Despite the US public hospitals being more likely to report a higher number of units using Lean, a higher daily management system index and use of Lean tools, Italian hospitals report more achievements primarily due to Lean. Further research can build on these findings by examining the relationship between Lean adoption/implementation and independent, objective performance measures.